Evaluation of the pre-detective signal priority for bus rapid transit: coordinating the primary and secondary intersections - Yang, Min; Sun, Gang; Wang, Wei; Sun, Xin; Ding, Jian; Han, Jing (Transport, 2018)
Since the traditional transit priority strategy can only adjust signal timing in a limited range and is not suitable for all kinds of signal timing designs, it cannot provide enough priority for Bus Rapid Transit (BRT). In addition, traditional transit priority strategy has caused serious interferences with other traffic. This study proposes a pre-detective signal priority strategy for BRT with coordination between primary and secondary intersections. By pre-detecting, the time buses arrive at the primary intersection, the signal timing of both the primary and secondary intersections, along with the offsets, are adjusted simultaneously, based on the common length and the green ratio of each phase. In this method, the signal cycle constraints are clarified, and the bus control coordination between intersections has been taken into consideration. In this paper, one direction traffic is taken as a study example to testify the effectiveness of this method. The study uses the data collected from Changzhou, China, and a microscopic traffic simulation software PTV VISSIM with four simulation scenarios defined: no signal priority, traditional signal priority, pre-detective signal priority and pre-detective signal priority with coordination. This paper selects a set of indicators to evaluate the traffic operation for both public transit and private traffic. Results show that pre-detective signal priority with coordination is the most effective, with the total bus intersection delay decreases by 67.4% and the bus headway adherence declines by approximately 40% at all the primary and secondary stations of BRT line 1. Moreover, the negative effects that could happen with providing signal priority for BRT, such as increasing the delay and length of queue of private traffic at the intersections, are significantly reduced. First published online 28 January 2015